Spermiogenesis and sperm ultrastructure as sources of phylogenetic characters. The example of characid fishes (Teleostei: Characiformes) - Quagio-Grassiotto, Irani [UNESP]; Baicere-Silva, Clarianna Martins; Santana, Júlio César de Oliveira; Mirande, Juan Marcos (Elsevier, 2020)
Fish sperm morphology is quite diverse. In the last decades our and other studies on Teleostei, mainly on Ostariophysi with emphasis in the Characiformes, have showing that the features of these spermatozoa can be used in phylogenetic analyses. Our purpose in this review is explaining how we can get data from sperm to be used for phylogenetic inference. The shape of the nucleus, midpiece and flagellum; the relative position of the centrioles; the number and distribution of a few organelles (mitochondria and vesicles) are features to be analyzed. To recognize homologies in the ultrastructural features of spermatozoa the types of spermatogenesis and spermiogenesis variations also need to be known. Other reproductive characters that have phylogenetic signal are also reviewed, among them the presence of insemination, the organization of the germinal epithelium, the internal structure of the testis. Here we also explain how to prepare testis for extraction of sperm morphological characters and how treat these characters. Lastly, we propose (supplementary material) two lists of characters defined for the Characiformes, that may serve as examples of how spermatic features may be used for phylogenetic analyses.
Keywords: Phylogeny; Sperm morphology; Spermatogenesis; Spermatozoa; Teleosts